2021
DOI: 10.3389/fmolb.2021.608369
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a DNA Repair Gene Signature and Establishment of a Prognostic Nomogram Predicting Biochemical-Recurrence-Free Survival of Prostate Cancer

Abstract: Background: The incidence of prostate cancer (PCa) is high and increasing worldwide. The prognosis of PCa is relatively good, but it is important to identify the patients with a high risk of biochemical recurrence (BCR) so that additional treatment could be applied.Method: Level 3 mRNA expression and clinicopathological data were obtained from The Cancer Genome Atlas (TCGA) to serve as training data. The GSE84042 dataset was used as a validation set. Univariate Cox, lasso Cox, and stepwise multivariate Cox reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Interestingly, in a study of prostatic adenocarcinoma cells, increased expression of the POLM gene was reported, which is in line with the results of the current study. It has also been suggested increased expression is because of the ine ciency of the HR repair pathway (20). Also, in studies on gastric and breast cancerous tissues, an increase in the XRCC4 gene expression was reported (21,22).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, in a study of prostatic adenocarcinoma cells, increased expression of the POLM gene was reported, which is in line with the results of the current study. It has also been suggested increased expression is because of the ine ciency of the HR repair pathway (20). Also, in studies on gastric and breast cancerous tissues, an increase in the XRCC4 gene expression was reported (21,22).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, in a study of prostatic adenocarcinoma cells, increased expression of the POLM gene was reported, which is in line with the results of the current study. It has also been suggested increased expression is because of the ine ciency of the HR repair pathway (19). Also, in studies on gastric and breast cancerous tissues, an increase in the XRCC4 gene expression was reported (20,21).…”
Section: Discussionmentioning
confidence: 98%
“…Thirty patients with H. pylori infection and moderate chronic gastritis were regarded as case group (Mean age of 50.10 years including 14 (46.66%) female, 16 (53.33%) Male) and the remaining 30 H. pylori negative patients who showed mild chronic gastritis patients were regarded as control group (Mean age of 47.07 years including 19 (63.33%) female(19) and 11 (36.66%) Male) .…”
mentioning
confidence: 99%
“…The gene BRCA2 is involved, together with BRCA1 , in DNA repair, cell cycle checkpoint regulation and transcription [ 63 ]. Several studies have identified DNA repair gene signatures as effective predictors of PC progression and outcome [ 47 , 64 ] It is currently understood that the normal protein product of BRCA2 gene is important in double-strand DNA repair by maintaining genomic integrity, and that once this gene is mutated or altered, DNA damage may not be repaired properly, likely leading to the occurrence of cancer. How DNA repair is affected by homeostatic processes involving life habits and stress responses is not sufficiently understood.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a priori approach to select a very specific set of genes involved in the processes detailed above. The advantage of this approach over a more traditional search for cluster of highly related genes [ 46 , 47 ] is related to the ability to look for connections with the behavioral output associated with the disease onset and progression. Therefore, the main aim of this study was to develop an innovative model based on the expression of regulatory genes associated with the stress and immune responses influencing cell proliferation.…”
Section: Introductionmentioning
confidence: 99%